"I'm stressed!": The work effect of process innovation on mental health - Yuhong Du; Hazrul Shahiri; Xiahai Wei (Elsevier, 2023)
Objectives: The prevalence of unmet mental healthcare needs is a common challenge faced by many developing countries. This situation may worsen if more attention is not paid to the dramatic changes in the industrial workplace because of the diffusion of new automation and robotisation in the process of production.We aim to examine whether mental health problems are associated with frontline workers' direct experience of process innovation in the firms where they operate and verify whether/which of these mechanisms are involved in this relationship. Methods: Our data were obtained from the Foshan Workplace Employee Survey (FWES). Mental health was proxied by the subjective assessment of workers' need to receive psychological counselling or treatment. To address endogeneity concerns, this study employed an extended ordered probit model and the two-stage least squares (2SLS) method. Results: Frontline workers employed in innovative manufacturing firms are significantly more likely than those in firms taking no such action to experience psychological difficulties and to seek psychological counselling or treatment. Firms with a higher likelihood of upgrading their production process are more capable of taking a range of measures to significantly but not sufficiently mitigate the psychological problems of their workers induced by process innovation. In workplaces with a new advanced automation environment, workers believe that they face higher job insecurity (JI) and work stress, which in turn is partially and effectively linked to the deterioration in their mental health and further increases treatment-seeking behaviours. Conclusion: This study suggests that carrying out process innovation is associated with increased psychological distress and, hence, more needs for mental healthcare services. To narrow the treatment gap originally subject to existing obstacles, it is necessary to face the new challenges posed by automation-induced change in the workplace, which policies should be particularly attentive to.